Genetic sources and diversity of the paddy field carp in the Pearl River basin inferred from two mitochondrial loci - Zhong, Zaixuan; Fan, Jiajia; Su, Huanhuan; Li, Yaya; Ma, Dongmei; Zhu, Huaping (Frontiers in Ecology and Evolution, 2022)
Paddy field carp (PF-carp) is an economically important fish cocultured with rice in traditional agricultural systems. Several distinctive strains of PF-carp have been formed through years of artificial and cross breeding. There is a concern about the status of germplasm resources among PF-carp, since little is known about the genetic sources, diversity, or differentiation. In this study we collected 17 PF-carp populations covering Daotian carp (DTL), Ru Yuan No.1 (RY), Jinbian carp (JBL), Shaijiang carp (SJL), and Wu carp (WL) along the Pearl River basin to explore their genetic sources and diversity using concatenated sequences of the mitochondrial cytochrome b gene and the D-Loop region. According to the haplotype network analyses, 1, 9, and 57 haplotypes originated from Cyprinus carpio carpio, Cyprinus carpio haematopterus and Cyprinus carpio rubrofuscus, respectively, confirming that genetic introgression has occurred in Pearl River PF-carp populations and Cyprinus carpio carpio was the most common species for genetic origin. The results showed that RY exhibited the lowest level of nucleotide diversity (π = 0.0011) due to high-intensity breeding and was significantly differentiated from the other four strains. PF-carp strains in these remote traditional systems tended to experience artificial selection and a lack of farmer connection that gradually increased genetic differentiation among strains. Notably, three populations of JBL exhibited significant high-level differentiation, since they originated from mountainous areas hindering farmers from fry exchange. In contrast, no significant differentiation was uncovered in the WL populations, since this strain is the most popular cultured strain and has undergone artificial exchange of parents and fry in many cultured regions. This study helps us to understand the status of germplasm resources among PF-carp and to trace their genetic origin before being introduced for local cultivation.